2021
DOI: 10.1016/j.nmd.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, physical activity and associated factors in 779 patients with myasthenia gravis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…MG patients were less active than controls and did not meet the WHO recommendations for physical activity. An association between moderate or high levels of physical activity and low levels of fatigue was found in a cross‐sectional study of 779 Danish MG patients [92]. Similarly, lower fatigue scores were found in physically active Dutch patients [96].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…MG patients were less active than controls and did not meet the WHO recommendations for physical activity. An association between moderate or high levels of physical activity and low levels of fatigue was found in a cross‐sectional study of 779 Danish MG patients [92]. Similarly, lower fatigue scores were found in physically active Dutch patients [96].…”
Section: Resultsmentioning
confidence: 95%
“…Studies have examined habitual physical activity in patients by questionnaires [92], accelerometer [93,94], or in combination [95]. MG patients were less active than controls and did not meet the WHO recommendations for physical activity.…”
Section: Physical Activity and Trainingmentioning
confidence: 99%
“…The decline in walking performance was gradual in MG patients, and the average distance covered in the 60s decreased significantly in MG patients 9 . Another study stated that the average value of walking speed in MG patients reached 1.54 and 1.51 m/s 26 .…”
Section: Discussionmentioning
confidence: 96%
“…Several statements say that subjective fatigue affects walking ability, but objective fatigue impacts individual weakness, meaning it impacts the quality of walking capability, not ability 28 . Previous studies assessed the relationship between fatigue and walking endurance in MG patients using the 6-minute walking test, which found a decrease in walking speed between the first and sixth min 26 . Other studies have shown that central and peripheral fatigue do not affect the speed of muscle contraction during submaximal force.…”
Section: Discussionmentioning
confidence: 99%
“…Eye problems and fatigue were also among the most discussed symptoms, reflecting a pattern of symptoms seen in real-world observational studies 7 . Fatigue is common in MG, particularly among women and those with more severe disease 30 , 37 , 38 , and is an important indicator of worsening quality of life 30 , 39 . While one domain of fatigue relates to the muscular disorder that impacts patients’ functional performance (peripheral fatigue), another is independent of muscle weakness, relating to a lack of energy and feelings of tiredness that interfere with patients’ mental and/or physical activities (central fatigue) 30 , 39 .…”
Section: Discussionmentioning
confidence: 99%